The influence of the five-factor model of personality on performance in competitive sports: a review - Shuai, Ying; Wang, Shaoshen; Liu, Xian; Kueh, Yee Cheng; Kuan, Garry (Frontiers in psychology, 2023)
Personality is considered to be a factor affecting athletic performance. However, inconsistency in the research results regarding size and even direction of the relationship. An evaluation of the evidence of the relationship between personality and athletic performance was conducted in order to summarize the evidence available. A systematic literature search was conducted in March 2023. Sport performance and the Big Five personality model were identified in our research. We used PubMed, Web of Science, Embase, Cochrane Library, Wang Fang (Chinese), Wei Pu (Chinese), and CNKI (Chinese) databases for the systematic literature search (Prospero registration number: CRD42022364000), screened 4,300 studies, and found 23 cross-sectional studies eligible for inclusion in this review. The results of this systematic analysis show that, besides neuroticism, openness, conscientiousness, extraversion, and agreeableness are all positively correlated with sports performance. Conscientiousness and extraversion are the two main personalities in team sports. Openness and agreeableness show different results in different sports, and it is not clear to which project they are beneficial. The value of personality as a possible predictor of athletic performance is generally positive. Therefore, professionals such as applied sports psychologists, coaching personnel, athletes, and sports administrators must comprehensively grasp the significance of personality’s role in achieving success in major competitions. Considering these facts, sports practitioners should promote personality screening and personality development programs.